Identification of antimycobacterial from actinobacteria (INACC A758) secondary metabolites using metabolomics data - Maya Dian Rakhmawatie; Mustofa; Puspita Lisdiyanti; Pratiwi, Woro Rukmi; Wibawa, Tri (Penerbit Universiti Kebangsaan Malaysia, 2022)
Actinobacteria produce active secondary metabolite with medicinal properties, such as antibacterial or anticancer. However, there are some reports about the difficulties in discovering novel secondary metabolites. Therefore, the need for a new approach is obvious. Several factors such as types of nutrients in the culture media or different solvents used for extraction have been proven to influence the Actinobacteria secondary metabolite production. In this study, a combination of culture media optimization and metabolites fingerprint analysis were applied to identify antimycobacterial active compounds from Actinobacteria (InaCC A758). Five culture media were used in the secondary metabolite production of the Actinobacteria. The metabolite fingerprinting was carried out by analyzing the secondary metabolite profile extracted from culture media optimization using UPLC-MS. Multivariate analysis, i.e. cluster analysis and principal component analysis (PCA) was applied. The result showed that a unique antimycobacterial compound candidate against Mycobacterium smegmatis was produced by SYP media cultured InaCC A758 (MIC 6.25 μg/mL).